2017
DOI: 10.1016/j.bbadis.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of BDNF cleavage by plasminogen-activator inhibitor-1 contributes to Alzheimer's neuropathology and cognitive deficits

Abstract: Brain-derived neurotrophic factor (BDNF) plays pivotal roles in neuronal function. The cleaved - mature - form of BDNF (mBDNF), predominantly expressed in adult brains, critically determines its effects. However, insufficient proteolytic processing under pathology may lead to the precursor form of BDNF (proBDNF) and thereby increased neuronal apoptosis and synaptic weakening. Previous findings in our lab showed that cognitive stimulation (CS) delayed memory decline in Tg2576 mouse model of Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…The data exposed above suggest that one of the possible mechanisms by which soluble Aβ forms affect synaptic function is linked to the changes observed in the tPA/PAI-1 system and, consequently, to the effects on pro-BDNF/BDNF ratio (Figure 1). Supporting this hypothesis, a recent study 54 with a mouse genetic model of familial AD (Tg2576) and post-mortem brain tissues has shown that Aβ soluble forms might impair BDNF proteolytic processing through modulation of neuronal PAI-1.…”
Section: Pathog Eni C Mechanis M Of a β Solub Le Forms In Ad Througmentioning
confidence: 95%
See 3 more Smart Citations
“…The data exposed above suggest that one of the possible mechanisms by which soluble Aβ forms affect synaptic function is linked to the changes observed in the tPA/PAI-1 system and, consequently, to the effects on pro-BDNF/BDNF ratio (Figure 1). Supporting this hypothesis, a recent study 54 with a mouse genetic model of familial AD (Tg2576) and post-mortem brain tissues has shown that Aβ soluble forms might impair BDNF proteolytic processing through modulation of neuronal PAI-1.…”
Section: Pathog Eni C Mechanis M Of a β Solub Le Forms In Ad Througmentioning
confidence: 95%
“…Injection of Aβ 1‐40 into CA1 region of the hippocampus of mice lacking tPA or plasminogen causes a strong PAI‐1 accumulation but not in the wild type. In addition, primary cortico‐hippocampal cultures from mouse AD model (Tg2576) cultured in the presence of the pathogenic fragment Aβ25‐35 immediately show a dramatic increase in PAI‐1 synthesis through activation of JNK‐dependent c‐Jun pathways …”
Section: Mechanism Of Action Of Aβ On the Plasminogen Activation Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…BDNF has been implicated in the modulation of energy balance [10], as alterations in its expression levels and activities result in a number of neurodegenerative disorders, covering Huntington disease, Alzheimer disease and Parkinson disease [11] ; [12]. Heretofore, it was not yet identified whether abdominal radiotherapy influenced BDNF expression in the brain.…”
Section: Introductionmentioning
confidence: 99%